Consumer Ethnocentrism and Generational Purchase Intentions for Indigenous Products - Chauhan, Richa; Kaul, Vidhi; Yadav, Sapna; Sanwal, Tanushree; Avasthi, Sandhya; Shah, Gaurav (Indian Journal of Marketing, 2026)
Purpose : This study aimed to examine the impact of consumer ethnocentrism on purchase willingness for indigenous products, particularly khadi, across different generational cohorts in India. It also investigated the mediating role of direct and indirect role models in influencing consumer behavior. Methodology : A quantitative research design was adopted using a structured questionnaire to collect primary data from consumers in metropolitan cities in India. A total of 238 valid responses were analyzed and categorized into Baby Boomers, Generation X, and Generation Y. One-way ANOVA and post hoc tests were used to examine generational differences, while multiple regression analysis was conducted to assess the influence of consumer ethnocentrism and role models on purchase willingness across cohorts. Findings : The results indicated significant generational differences in consumer ethnocentrism. Ethnocentrism was found to be a significant predictor of purchase willingness among Baby Boomers and Generation X. However, for Generation Y, neither consumer ethnocentrism nor role models significantly influenced purchase willingness. Research Limitations/Implications : The study is limited to metropolitan consumers and a specific cultural product (khadi), which may restrict generalizability. Future research could expand to other regions, product categories, and generational groups. Practical Implications : The findings provided insights for policymakers and marketers to design targeted strategies for promoting indigenous products by considering generational differences and leveraging ethnocentric tendencies. Originality/Value : This study contributed to the literature by integrating consumer ethnocentrism, generational cohort analysis, and role model influence in the context of indigenous product consumption in India.